1995
DOI: 10.1006/dbio.1995.1024
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Characterization, and Developmental Expression of a Rat Lung Alveolar Type I Cell Gene in Embryonic Endodermal and Neural Derivatives

Abstract: We report here the identification and characterization of a novel gene, T1 alpha, expressed in high abundance in adult rat lung, fetal lung, and early fetal brain. T1 alpha was identified by a monoclonal antibody previously shown to be specific for an antigen expressed by alveolar epithelial type I cells. The cDNA for T1 alpha is 1.85 kb and identifies a single mRNA species of the same size on Northern blots of adult rat lung. The longest open reading frame of the cDNA is 498 bases which would encode a protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
189
0
5

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(209 citation statements)
references
References 0 publications
15
189
0
5
Order By: Relevance
“…OTS-8 was isolated as a phorbol ester-inducible gene from cultured osteoblasts (Nose et al, 1990), and gp38 was described as a marker of stromal cells in T-cell-dependent areas of peripheral lymphoid tissues (Farr et al, 1992). The rat (T1␣/E11/podoplanin), canine (gp40), and human (gp36) homologs to murine PA2.26 have also been reported by different laboratories (Breiteneder-Geleff et al, 1997;Rishi et al, 1995;Wetterwald et al, 1996;Zimmer et al, 1997Zimmer et al, , 1999. All these proteins have similar biochemical characteristics and tissular distributions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OTS-8 was isolated as a phorbol ester-inducible gene from cultured osteoblasts (Nose et al, 1990), and gp38 was described as a marker of stromal cells in T-cell-dependent areas of peripheral lymphoid tissues (Farr et al, 1992). The rat (T1␣/E11/podoplanin), canine (gp40), and human (gp36) homologs to murine PA2.26 have also been reported by different laboratories (Breiteneder-Geleff et al, 1997;Rishi et al, 1995;Wetterwald et al, 1996;Zimmer et al, 1997Zimmer et al, , 1999. All these proteins have similar biochemical characteristics and tissular distributions.…”
Section: Discussionmentioning
confidence: 99%
“…All these proteins have similar biochemical characteristics and tissular distributions. Thus, for example, rat T1␣ sialoglycoprotein was first described as a marker of alveolar type I epithelial cells of the lung (Rishi et al, 1995), and human gp36 has been recently characterized as a mucin-type transmembrane sialoglycoprotein expressed at the apical plasma membrane of the vascular endothelium and alveolar epithelium (Zimmer et al, 1999). Although canine gp40 can act as a main receptor for the influenza C virus (Zimmer et al, 1995), and rat podoplanin was found to be down-regulated in an experimental model of minimal-change nephropathy (Breiteneder-Geleff et al, 1997), the biological functions of these proteins are unknown.…”
mentioning
confidence: 99%
“…In normal human tissue, podoplanin is expressed in kidney podocytes (Breiteneder-Geleff et al, 1999), in skeletal muscle, placenta, lung and heart (Martin-Villar et al, 2005), in myofibroblasts of the breast and salivary glands, in osteoblasts and mesothelial cells (Ordonez, 2006b). It is also expressed on the apical surface of rat alveolar type I cells (Rishi et al, 1995). Occasionally, focal expression of podoplanin can be found in circumscribed areas of the basal layer of the human epidermis (Schacht et al, 2005).…”
Section: Podoplanin Is Expressed In Most Human Tissuesmentioning
confidence: 99%
“…At the saccular stage, type I cells increase in proportion lining the alveolar walls, providing a short diffusion pathway for gas exchange (Warburton et al, 2000;Compernolle et al, 2002;Chinoy, 2003). They express specific markers like aquaporin 5 (Aqp-5) and glycoprotein T1␣ (Rishi et al, 1995;Funaki et al, 1998;Williams, 2003).…”
Section: Introductionmentioning
confidence: 99%